Experimental investigation on eucalyptus sawdust torrefaction for energy properties upgrading Investigação experimental na torrefação da serragem de eucalipto para aprimoramento de propriedades energéticas - Da Silva, Robson Leal; Patelli Júnior, José Ricardo; Seye, Omar; Michels, Carolina Santana; De Paula, Isabele Oliveira [UNESP]; Schneider, Paulo Smith (Instituto de Pesquisa e Estudos Florestais (IPEF), 2020)
Wood harvesting presents excellent productivity in Brazil, which is one of the largest producers worldwide, Eucalyptus mainly. Torrefaction as a thermal treatment for woody biomass (Eucalyptus) was evaluated to improve its energy characteristics as material for combustion with biomass valuation. The methodology considered the torrefaction process with nine combinations, three residence times (20, 40 and 60 minutes) and three reaction temperatures (180, 220 and 260°C) for wood samples. Quality aspects and quantitative parameters were determined experimentally, literature correlations and equations (proximate and ultimate analyzes, hygroscopicity, HHV, mass and energy yields). Main conclusions are: A) Hygroscopicity decreases (increasing hydrophobicity) providing a better storage condition aiming at commercialization; b) Volatile matter and fixed carbon contents are improved, δTVM,db=-4.7% and δTFC,db =+5.3%, while H/C and O/C ratios tend to lower values when enhancing its quality; c) The darker the biomass after roasting (biochar), the better are its quality for energy purposes; d) Biomass upgrading occurs when increasing its HHV (up to 5.1%, from 18.62 up to 19.58 MJ.kg-1), even with energy yield lowering when intensifying torrefaction (nE-Yield down to 0.9451); e) Torrefacted biomass (char) corresponds to intermediate energy properties between raw biomass and charcoal.
Keywords: Biomass pretreatment; Industrial applications.; Pyrolysis; Renewable energy; Solid biofuel